A history of great ideas in abnormal psychology - Weckowicz, Thaddeus E. (Advances in psychology (Amsterdam, Netherlands) ;, 1990)
As indicated by its title "A History of Great Ideas in Abnormal Psychology", this book is not just concerned with the chronology of events or with biographical details of great psychiatrists and psychopathologists. It has as its main interest, a study of the ideas underlying theories about mental illness and mental health in the Western world. These are studied according to their historical development from ancient times to the twentieth century. The book discusses the history of ideas about the nature of mental illness, its causation, its treatment and also social attitudes towards mental illness. The conceptions of mental illness are discussed in the context of philosophical ideas about the human mind and the medical theories prevailing in different periods of history. Certain perennial controversies are presented such as those between the psychological and organic approaches to the treatment of mental illness, and those between the focus on disease entities (nosology) versus the focus on individual personalities. The beliefs of primitive societies are discussed, and the development of early scientific ideas about mental illness in Greek and Roman times. The study continues through the medieval age to the Renaissance. More emphasis is then placed on the scientific revolution of the seventeenth century, the enlightenment of the eighteenth, and the emergence of modern psychological and psychiatric ideas concerning psychopathology in the twentieth century.